A proposed framework for sustainable international partnerships: lessons learned in rural Uganda - Carol C Chen; Andrea T Cruz; Heather Honoré Goltz; Esther M Sampayo (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background International non-governmental organizations (NGOs) have widespread experience building health-related programs; however, few studies have examined local stakeholder perceptions of their collaboration and sustainability. # Objective To describe attitudes and beliefs of five stakeholder groups concerning the building of a healthcare facility in rural Uganda by an international NGO, with the goal of developing a potential framework. # Methods A qualitative study was conducted using focus groups, semi-structured interviews, and open-ended questionnaires. The five participating stakeholder groups included: community members, community leaders, healthcare workers, NGO leaders, and representatives from the Ugandan Ministry of Health. # Results All 40 participants reported interest in working together and four principal themes were identified: crucial building blocks of a healthcare facility; expectations regarding collaborative relationships; key deliverables desired by the community; and specific obstacles to sustainability. # Conclusions Participating stakeholders believe that the most important components of sustainable healthcare facilities are the establishment of two-way partnerships within the community and an emphasis on deliverables such as education, higher standards of care, and maintainable infrastructure. Unique obstacles must also be recognized. We propose a conceptual framework that may be applied to future public health interventions in resource-limited, international settings.